Game Schedules and Rate of Concussions in the National Football League. Issue 11 (23rd November 2017) - Teramoto, Masaru; Cushman, Daniel M.; Cross, Chad L.; Curtiss, Heather M.; Willick, Stuart E.
Background: Concussion prevention in the National Football League (NFL) is an important priority for player safety. The NFL now has modified game schedules, and one concern is that unconventional game schedules, such as a shortened rest period due to playing on a Thursday rather than during the weekend, may lead to an increased risk of injuries. Hypothesis: Unconventional game schedules in the NFL are associated with an increased rate of concussion. Study Design: Descriptive epidemiological study. Methods: This study analyzed concussions and game schedules over the NFL regular seasons from 2012 to 2015 (4 years). Documented numbers of concussions, identified by use of the online database PBS Frontline Concussion Watch, were summarized by regular-season weeks. Association of days of rest and game location (home, away, or overseas) with the rate of concussion was examined by use of the χ 2 test. Logistic regression analysis was performed to examine the relationships of days of rest and home/away games to the risk of repeated concussions, with adjustment for player position. Results: A total of 582 concussions were analyzed in this study. A significantly greater number of concussions occurred in the second half of the season ( P < .01). No significant association was found between the rate of concussion and the days of rest, game location, or timing of the bye week by the team or the opponent ( P > .05). Game schedules were not significantly associated with the occurrence of repeat concussions ( P > .05). Conclusion: Unconventional game schedules in the NFL, including playing on Thursday and playing overseas, do not seem to put players at increased risk of concussions.